Progranulin, a Major Secreted Protein of Mouse Adipose-Derived Stem Cells, Inhibits Light-Induced Retinal Degeneration. (14th November 2013) - Tsuruma, Kazuhiro; Yamauchi, Mika; Sugitani, Sou; Otsuka, Tomohiro; Ohno, Yuta; Nagahara, Yuki; Ikegame, Yuka; Shimazawa, Masamitsu; Yoshimura, Shinichi; Iwama, Toru; Hara, Hideaki
Abstract : The authors examined the protective effects of adipose-derived stem cells and adipose-derived stem cell-conditioned medium (ASC-CM) against retinal damage and identified the neuroprotective factors in ASC-CM. The findings suggest that ASC-CM and progranulin have neuroprotective effects in the light-induced retinal-damage model. Progranulin may be a potential target for the treatment of the degenerative diseases of the retina. Abstract: : Adipose tissue stromal vascular fraction contains mesenchymal stem cells, which show protective effects when administered to damaged tissues, mainly through secreted trophic factors. We examined the protective effects of adipose-derived stem cells (ASCs) and ASC-conditioned medium (ASC-CM) against retinal damage and identified the neuroprotective factors in ASC-CM. ASCs and mature adipocytes were isolated from mouse subcutaneous tissue. ASCs were injected intravitreally in a mouse model of light-induced retinal damage, and ASC injection recovered retinal function as measured by electroretinogram and inhibited outer nuclear layer, thinning, without engraftment of ASCs. ASC-CM and mature adipocyte-conditioned medium were collected after 72 hours of culture. In vitro, H2 O2 - and light-induced cell death was reduced in a photoreceptor cell line with ASC-CM but not with mature adipocyte-conditioned medium. In vivo, light-induced photoreceptor damage was evaluated by measurement of outer nuclear layer thickness at 5 days after light exposure and by electroretinogram recording. ASC-CM significantly inhibited photoreceptor degeneration and retinal dysfunction after light exposure. Progranulin was identified as a major secreted protein of ASCs that showed protective effects against retinal damage in vitro and in vivo. Furthermore, progranulin phosphorylated extracellular signal-regulated kinase, cAMP response element binding protein, and hepatocyte growth factor receptor, and protein kinase C signaling pathways were involved in the protective effects of progranulin. These findings suggest that ASC-CM and progranulin have neuroprotective effects in the light-induced retinal-damage model. Progranulin may be a potential target for the treatment of the degenerative diseases of the retina.